The Inhibitory Effect of Aspirin on Fibrinolysis Is Reversed by Iloprost, a Prostacyclin Analogue - Bertelé, V; Mussoni, L; Pintucci, G; del Rosso, G; Romano, G; de Gaetano, G; Libretti, A (Thrombosis and Haemostasis, 1989)
The reduced fibrinolytic response after aspirin intake may be due to prevention of prostacyclin production. The effect of iloprost (a stable prostacyclin analogue) was tested on the fibrinolytic activity (euglobulin lysis area on fibrin plate [E.L.A.], t-PA antigen, PAI activity and PAI-1 antigen) of plasma drawn after venous stasis test from six healthy male volunteers, who each received all the following treatments according to a single-blind randomized cross-over design: placebo, iloprost, aspirin + placebo, aspirin + iloprost. The mean E. L. A. value after venous occlusion was significantly higher than the basal level after every treatment, but aspirin. Within each treatment group the t-PA antigen levels in response to venous stasis were significantly higher than the basal ones. PAI-1 antigen levels did not change significantly before and after venous stasis either within or among the treatment groups. These data are consistent with the hypothesis that the mechanism related to aspirin’s effect on fibrinolysis is mediated by suppression of vessel wall prostacyclin production. Aspirin’s inhibitory effect on fibrinolysis was in fact prevented by replacing endogenous prostacyclin with iloprost. Iloprost enhances fibrinolytic activity reduced by aspirin, but not by promoting t-PA release or by inhibiting release of the specific inhibitor, PAI-1.
Keywords: Aspirin; Fibrinolytic activity; Prostacyclin analogues